PENGARUH GAME BASED LEARNING MENGGUNAKAN APLIKASI KAHOOT! TERHADAP PENINGKATAN KOSAKATA BAHASA ARAB SISWA KELAS XII MA MIFTAHUL FALAH PURWODADI - hidayatulloh, ahsan; Rokhmatulloh, Nur (Universitas Muhammadiyah Mataram, 2024)
Vocabulary is an important part of language that can affect students in mastering it. Kahoot is one of the proposed learning media to increase students' understanding of Arabic vocabulary. Therefore, this study aims to determine whether or not there is a significant effect of using Kahoot as a game-based learning medium on increasing the Arabic vocabulary of twelfth grade students of MA Miftahul Falah. This research is a pre-experimental study which uses a one group pretest posttest design, so there will be a multiple choice final test at the end of the treatment period. The results showed that the sig. the t-test is 0.000, which is less than 0.05. This shows that there is a significant influence between the use of Kahoot as a learning medium for twelfth grade students in mastering vocabulary at MA Miftahul Falah Purwodadi Keywords: Effect, Vocabulary Improvement, Game-Based Learning, Kahoot!